Interactive effects of basin features and land-use change on macroinvertebrate communities of headwater streams in the Patagonian Andes - Miserendino, Maria Laura (2004)
Composition and structure of macroinvertebrate communities were documented in relation to hydrochemical variables over a 10-month period in four headwater tributaries of the Futaleufú River, northwestern Chubut, Argentina. The streams are located along the strong rainfall gradient that decreases from west to east and they have different basin features. At Blanco and Baggilt streams, riparian vegetation consisted primarily of native Nothofagus forest, while in the Nant y Fall and Rifleros, basins with a long legacy of domestic grazing, the introduced Salix fragilis was the dominant riparian species. Macroinvertebrate species richness, density, and biomass were similar among rivers; however, biomass of shredders was highest in the Nothofagus forested streams and collector-filterers were significantly higher in Salix fragilis-bordered rivers. Water temperatures were higher in non-native Salix sites than in the native or mixed forested sites. Canonical community analysis indicated community composition was related to geomorphic attributes of the rivers, especially slope, basin height (elevation change), distance to the source, substratum size, and Salix coverage. Moreover, seasonally dynamic variables, rainfall and water temperature were good community predictors. Land-use change (conversion from Nothofagus to pastures and the Salix fragilis invasion in the riverbanks of pasture-dominated catchments) was interactive with natural stream attributes as determinants of macroinvertebrate distribution and abundance.